ANALISIS PERENCANAAN STRATEGI PERUSAHAAN MENGGUNAKAN METODE BALANCED SCORECARD DAN HOSHIN KANRI PADA PT. IBE - Yovi Yostika; Ahmad; Doaly, Carla Olivia (Jurnal Mitra Teknik Industri, 2023)
In increasingly fierce business competition, companies must have a strategic plan that aims to focus on achieving long-term goals by linking organizational strategic plans. PT. IBE is a company in Indonesia operating in the recycling of metal resources. In carrying out its duties, the company currently only focuses on finances to be able to win the competition in the industrial world, so that other aspects are not considered. Thus, PT. IBE needs to measure company performance so that it can set targets and performance in company assessments. In measuring this performance, the Balanced Scorecard (BSC) approach is used by describing the company's vision and mission into 4 perspectives, namely Finance, Customers, Internal Business Processes, and Learning and Growth which have weights of 0.314, 0.247, 0.201 and 0.239 respectively. In this study sparked 12 Key Performance Indicators (KPI), Objective Matrix (OMAX) and the Traffic Light System assessment system and found that there were 2 KPI indicators that were already good, 5 KPI indicators had not been achieved but were close to the target, and 5 KPI indicators were still far away. under targets. After that, strategic planning is carried out using Hoshin Kanri using the Hoshin planning X-Matrix in order to achieve long-term goals and strengthen the vision and mission statement that the company expects to continue to grow.